Pleural Resident Macrophages and Pleural IRA B Cells Promote Efficient Immunity Against Pneumonia by Inducing Early Pleural Space Inflammation - Bénard, Alan; Podolska, Malgorzata J.; Czubayko, Franziska; Kutschick, Isabella; Klösch, Bettina; Jacobsen, Anne; Naschberger, Elisabeth; Brunner, Maximilian; Krautz, Christian; Trufa, Denis I.; Sirbu, Horia; Lang, Roland; et al. (Frontiers in Immunology, 2022)
Airway infection is a major cause of mortality worldwide. The identification of new mechanisms aiding in effective host immune response is therefore required. Here, we show that the specific depletion of the pleural immune cell compartment during bacterial pneumonia resulted in a reduced pulmonary immune response and increased mortality in mice. Bacterial airway infection provoked early pleural space (PS) inflammation characterized by innate response activator (IRA) B cell development and pleural large resident macrophage (LRM) necroptosis, the repopulation of LRMs being driven by cellular proliferation in situ. Necroptotic LRMs amplified PS inflammation by stimulating pleural Mincle-expressing macrophages whereas IRA B cells contributed partially to GM-CSF-induced PS inflammation. Upon pulmonary infection, the induction of PS inflammation resulted in reduced bacterial burden whereas the specific depletion of pleural resident macrophages led to increased mortality and bacterial burden and reduced pulmonary immunity. Moreover, mice in which B cells were unable to produce GM-CSF exhibited reduced CD103+ dendritic cells and reduced CD4+ T cell numbers in the draining lymph node. Altogether, our results describe a previously unrecognized mechanism of pleural space inflammation necessary for effective protection against bacterial airway infection.